Role of Dexamethasone and Methylprednisolone Corticosteroids in Coronavirus Disease 2019 Hospitalized Patients: A Review - Mehta, Jyoti; Rolta, Rajan; Mehta, Brij Bhushan; Kaushik, Neha; Choi, Eun Ha; Kaushik, Nagendra Kumar (Frontiers in Microbiology, 2022)
The World Health Organization (WHO) announced the Coronavirus Disease 2019 (COVID-19) as a pandemic disease globally on 11 March, 2020, after it emerged in China. The emergence of COVID-19 has lasted over a year, and promising vaccine reports have been produced, we still have a long way to go until such remedies are accessible to everyone. Now, the use of corticosteroids to combat the virus's strong inflammatory impacts has moved to the forefront in management for patients seeking supplemental oxygen. A goal of this review is to illuminate two corticosteroids i.e. Dexamethasone and methylprednisolone in terms of their chemical and physical properties, role in COVID-19 patients suffering from pneumonia, the proposed mode of action in COVID-19, pharmacokinetics, pharmacodynamics, interaction with other drugs, and contradiction to explore the trends and perspectives for future research. Literature was searched from scientific databases such as Science Direct, Wiley, Springer, PubMed, books for the preparation of this review. The RECOVERY trial, a massive, multidisciplinary, randomized, and open-label trial is mainly accountable for recommendations over the usage of corticosteroids in COVID-19 patients. The corticosteroids such as dexamethasone and methylprednisolone in the form of medication have anti-inflammatory, analgesic, and anti-allergic characteristics, including the ability to inhibit the immune system. These drugs are also recommended for curing multiple ailments such as rheumatic and autoimmune diseases, leukemia, multiple myeloma, Hodgkin's and non-Hodgkin's lymphoma along with other drugs. Toxicology studies proved them safe usually at low dosage via oral or other routes.